The relationship between food production and consumption variability: Policy implications for developing countries - Sahn, David E.; von Braun, Joachim (Wiley, 1987)
This paper examines whether there is increased inter‐year instability in food consumption at the national level, and to what extent this is attributable to increased instability of food production in the wake of adoption of modern agricultural technology. The data analysed indicates that increased production instability does translate into increased fluctuations in consumption. Nevertheless, year‐to‐year consumption variability among the sample of 38 countries has declined during the past 25 years. This is attributed to improved stocking operations and trade practices which accompany economic growth. Nevertheless, food insecurity, as measured in terms of fluctuations around trend levels of consumption, does remain a problem, especially among the poor. Therefore, policy options to reduce consumption instability are outlined.